2017
DOI: 10.1111/epi.13806
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of a multicomponent self‐management intervention for adults with epilepsy (ZMILE study)

Abstract: SUMMARYObjective: The objective of this (trial-based) economic evaluation was, from a societal perspective, to compare the cost-effectiveness of a multicomponent self-management intervention (MCI) with care as usual (CAU) in adult patients with epilepsy over a 12-month period. Methods: In a randomized-controlled trial, participants were randomized into intervention or CAU group. Adherence, self-efficacy (Epilepsy Self-Efficacy Scale [ESES]), quality-adjusted life years (QALYs), healthcare costs, production los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Instruments used to assess outcome measurements are shown in Table 1. The cost-effectiveness and the process evaluation of the ZMILE-study are reported elsewhere [21,22].…”
Section: Designmentioning
confidence: 99%
“…Instruments used to assess outcome measurements are shown in Table 1. The cost-effectiveness and the process evaluation of the ZMILE-study are reported elsewhere [21,22].…”
Section: Designmentioning
confidence: 99%
“… 18 Moreover, cost-effectiveness estimates for the ZMILE-intervention appeared to be promising. 19 Therefore, the ZMILE-intervention could prove to be a promising and cost-effective addition to the current standard care for adults with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized controlled trial, we compared ZMILE to the standard treatment for the evaluation of its clinical-and cost-effectiveness. 18,19 After completion of the randomized controlled trial, a process evaluation was performed and minor changes were made to the intervention. 20 One of the main changes concerns the use of e-health tools which was an important element of our multicomponent intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have looked at the cost of epilepsy in the UK. We know of a recent Dutch study in which a cost evaluation of a self-management course for epilepsy was undertaken 132 and have collaborated with the trial team in assessing the appropriateness of outcome measures for cost evaluations in epilepsy. 133 Data on health service use and QoL were collected with other secondary outcomes during the trial.…”
Section: Chapter 8 Health Economics Introductionmentioning
confidence: 99%
“…This is the second economic analysis of a complex intervention for epilepsy, and the first in the UK. 132 10. The economic analysis highlighted the health cost for poorly controlled epilepsy and the capacity burden placed by use of EDs, which is twice as much as for all PWE.…”
mentioning
confidence: 99%